Prevalence and determinants of hypertension among people living with HIV in Ghana: A cross-sectional study - Kasim Abdulai; Safianu Osman Aleboko; Isaac Anane; Ivan Addae-Mensah; Abdul-Malik Bawah (PLoS ONE, 2026)
Background Hypertension is a major health concern in Sub-Saharan Africa (SSA). People living with human immunodeficiency virus (PLHIV) face unique risks for cardiometabolic disorders. However, the factors associated with hypertension among PLHIV have been understudied in SSA. This study examines the prevalence and determinants of hypertension among PLHIV in Ghana. Methods A total of 440 PLHIV aged 18 years and older receiving antiretroviral therapy (ART) for a minimum of six months were recruited in this hospital-based cross-sectional study. Variables assessed included blood pressure, alcohol consumption, type of antiretroviral therapy (ART) medication, duration of exposure to ART, smoking history, age, sex, level of education, and exercise. Binary logistic regression was used to determine the factors associated with hypertension. Results The overall prevalence of hypertension was 33%. People living with HIV who were on second-line ART had a lower risk of hypertension compared to those on first-line ART (OR = 0.379; 95% CI: 0.169–0.846; p = 0.018). Similarly, participants with high muscle mass (OR = 0.177; 95% CI: 0.064–0.487; p < 0.01) and those with very high muscle mass (OR = 0.220; 95% CI: 0.051–0.943; p = 0.041) had a lower risk of hypertension compared to those with low muscle mass. In contrast, participants who were obese had approximately four times greater odds of hypertension compared to those with underweight (OR = 4.046; 95% CI: 1.018–16.083; p = 0.047). Additionally, participants with medium IDDS (OR = 1.968; 95% CI: 1.150–3.369; p = 0.014) and high IDDS (OR = 2.348; 95% CI: 1.078–5.115; p = 0.032) had about twice the risk of hypertension compared to those with low IDDS. Conclusion This study found a high prevalence of hypertension among PLHIV. Second-line ART may reduce the risk of hypertension, while higher muscle mass may have a protective effect. Further research is needed to better understand the impact of dietary diversity and specific dietary components on hypertension in this population.